Analisis Kemampuan Peserta Didik dalam Literasi Numerasi pada Soal Bilangan di Sekolah Dasar - Saripah Aini; Salmaini Safitri Syam; Chandra Chandra (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
The difficulties students experience when solving problems that require calculation indicate a need to improve their arithmetic skills. This research aims to describe students' numeracy skills in solving number problems while also identifying the obstacles they encounter in developing these skills. Specifically, this study explores the mathematical numeracy literacy abilities of fourth-grade elementary school students in facing the Minimum Competency Assessment (AKM) questions on number material at one elementary school in Indonesia. This research uses a descriptive qualitative approach with data collection techniques including AKM numeracy tests, observation, interviews, and documentation. The research findings show that students' mathematical numeracy literacy ability is in the moderate category, with an average achievement of 65.8%. The main difficulties experienced by students include: (1) recognizing mathematical information from contextual problems, (2) performing numerical calculations, (3) interpreting calculation results in the context of real-world problems, and (4) communicating mathematical reasoning in writing. Based on these results, this research recommends strengthening numeracy learning that connects material with everyday life contexts, as well as improving students' mathematical reasoning abilities through problem-based learning approaches, to optimize the mathematical numeracy literacy of elementary school students.